PENGARUH PEMBERIAN INSENTIF TERHADAP PENINGKATAN PRODUKTIVITAS KERJA PEGAWAI PADA PT. SUCOFINDO PERSERO JAKARTA - Boma Jonaldy Tanjung; Eka Darmawati (Pusat Riset dan Inovasi Nasional, 2022)
As workers, humans are required to be able to do their work effectively and efficiently. The meaning of effective is to achieve goals in accordance with the plans that have been set, while what is meant by efficient is workers who can use minimal resources to obtain the planned output so that the workforce is given a design to avoid a decrease in morale and aims to improve productivity. To reduce the decline in employee productivity, companies are required to be able to meet the needs of their employees. Given the purpose of employees in working to be able to meet the needs of his life well. Incentives are given to employees twice a year, so these incentives are given every 6 months. The amount of incentives given varies, depending on the work performance that has been achieved by the employee concerned. From the data on the development of employee absenteeism and employee turnover (LTO) for 5 years, it can be seen that there is a decrease. This reflects the reciprocal relationship between employees and the company that is created through the provision of incentives and welfare. Wisdom in providing incentives must be increasingly considered. With the development of the company, the demands of employees will also grow in an effort to meet their increasing needs, so it is better to provide incentives or employee welfare to be negotiated first with all employees. What form of program is desired and can be enjoyed by all employees.